2019
DOI: 10.1111/bjh.15761
|View full text |Cite
|
Sign up to set email alerts
|

Low burden of minimal residual disease prior to transplantation in children with very high risk acute lymphoblastic leukaemia: The NOPHO ALL2008 experience

Abstract: Summary The population‐based Nordic/Baltic acute lymphoblastic leukaemia (ALL) Nordic Society for Paediatric Haematology and Oncology (NOPHO) ALL2008 protocol combined minimal residual disease (MRD)‐driven treatment stratification with very intense first line chemotherapy for patients with high risk ALL. Patients with MRD ≥5% at end of induction or ≥10−3 at end of consolidation or following two high risk blocks were eligible for haematopoietic cell transplantation (HCT) in first remission. After at least three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…MRD was analyzed by RQ‐PCR according to the EuroMRD guidelines or by multicolor flow cytometry as described in the NOPHO ALL2008 guidelines . MRD results were categorized as either negative or positive < 10 −4 ; positive ≥ 10 −4 but <10 −3 ; positive ≥ 10 −3 ; or positive but below a quantitative range of 10 −3 …”
Section: Methodsmentioning
confidence: 99%
“…MRD was analyzed by RQ‐PCR according to the EuroMRD guidelines or by multicolor flow cytometry as described in the NOPHO ALL2008 guidelines . MRD results were categorized as either negative or positive < 10 −4 ; positive ≥ 10 −4 but <10 −3 ; positive ≥ 10 −3 ; or positive but below a quantitative range of 10 −3 …”
Section: Methodsmentioning
confidence: 99%
“…However, in a recent Nordic study with more patients included, CMV mismatch was associated with higher TRM underlining the significance of CMV infection for general outcome following HCT, also in children. 23 Acute GvHD grade 2-4 was not significantly associated with mortality. Schrecter et al have previously shown a lower mortality correlated with aGvHD after a second HCT possibly as children with aGvHD most often have neutrocyte take and thus be more resistant to, that is, bacterial infections.…”
Section: Discussionmentioning
confidence: 87%
“…5 NOPHO recently retrospectively examined HSCT outcomes in CR1 and reported a 5-year DFS of 79.1%. 25 Persistent MRD was the indication for HSCT in only 35% of this cohort, and 17% received a transplant without a protocol indication. The population studied differed from the COG AALL0232 population referenced above in several potentially relevant features; however, these and other promising results in CR1 led many to consider HSCT for persistent MRD, for example, the current prospective examination on the European trial AEIOP-BFM-ALL 2009.…”
Section: Persistent Mrdmentioning
confidence: 89%
“…Although HSCT is often considered for patients with anticipated poor survival with chemotherapy alone, relevant to this population, detectable MRD at the time of HSCT has been consistently associated with an increased risk of relapse, as is MRD post-HSCT. 23,25,27,40,41 Further intensification of chemotherapy to decrease or eliminate MRD and HSCT itself are not without significant risk of morbidity and mortality. 3,22,28,42 Therefore, the possibility of durable remission without consolidative HSCT is one aim of an ongoing trial developed by the COG and Novartis.…”
Section: Aall1721/cassiopeiamentioning
confidence: 99%